The neoliberal city as utopia of exclusion. Issue 1 (2nd January 2020) - Bailey, Mark
ABSTRACT: This paper critically examines the modern city as an expression of a neoliberal 'utopia of exclusion'. Beginning by outlining the utopian, exclusionary dimensions of contemporary neoliberalism, it moves on to argue that the modern city embodies the utopia of exclusion as an 'Evil Paradise'. However, the paper contends even at its most celebratory the 'Evil Paradise' evokes the dark side of the Utopia of exclusion: the increasingly absolute separation between the lives of the haves and the have-nots. The paper concludes by asking what potential alternatives exist in contemporary urban practices and asks if the utopia of exclusion itself paradoxically presents opportunities to construct alternative, inclusive forms of community.